Removal of emulsion droplets by immobilization in calcium alginate gel - Hayashi, Natsuko; Tanaka, Takanori; Yamada, Ryuhei; Jami, Mohammed Saedi; Iwata, Masashi (2013)

(untitled)
A novel technique utilizing particle immobilization in hydrogels has been proposed for a solid-liquid separation of difficult-to-filter colloidal suspensions. Fundamental aspects of this process are investigated using oil in water (O/W) emulsion as colloidal materials. A mixture of alginate aqueous solution and colloidal suspension is added dropwise to a calcium chloride aqueous solution, resulting in calcium alginate gel. Colloidal oil droplets are immobilized in the gel. The gel suspension is dehydrated gravitationally, followed by mechanical expression of the gel particles. During the expression, the colloidal oil components remain in the gel and the expressed liquid is clear. The expressed gel is then discarded. O/W emulsions are effectively treated by this method; i.e. leakages of oil into a supernatant of gel suspension and into a squeezed liquid were less than 6% and 3% of oil, respectively, both in kerosene-alginate mixture and cyclohexane-alginate mixture. It is confirmed that oil droplets in the gel network behave to interfere with the liquid flow in the gel particles during expression. From numerical analysis of simplex procedure, it is clarified that oil droplets were entrapped in gel network.